Complete response of advanced cutaneous squamous cell and basal cell carcinomas with sequential cemiplimab and sonidegib therapy. (2nd December 2021) - Weis, J.; Grote, C.; Weichenthal, M.; Hauschild, A.
Abstract: A 78‐year‐old woman was referred to our skin cancer centre with three previous incomplete resections in the left cavum conchae of a deep‐infiltrating locally advanced, but still asymptomatic basal cell carcinoma (BCC). The patient noted furthermore two rapidly growing exophytic lesions in the left preauricular and cervical area in the last weeks. The clinical and histological distinction of locally advanced from metastatic cutaneous squamous cell carcinoma (CSCC) lesions was challenging. Imaging analysis with CT scans showed, however, an involvement of the parotid gland as well as multiple small lymph node metastases. The interdisciplinary tumour board decision at our institution recommended a systemic treatment with the PD1‐antibody cemiplimab. After 13 cycles with cemiplimab at a dose of 350 mg intravenously every 3‐weeks, the patient showed a complete response of the two CSCC lesions with histological confirmation. However, the BCC of the left ear appeared to be unchanged and still asymptomatic. The interdisciplinary tumour board considered this tumour to be no candidate for a curative resection or irradiation. Therefore, the patient was exposed to the hedgehog inhibitor sonidegib with a conventional dose of 200 mg orally per day. After 3 months of treatment, the tumour showed a markable regression and a complete response was confirmed by 3‐punch biopsies from this preoperated lesion. Both cemiplimab and sonidegib were excellently tolerated with almost no adverse events apart from a mild fatigue (CTC grade 1) over the first 3 weeks of the cemiplimab therapy. There were no laboratory abnormalities found.